Retraction Note: Psychometric properties of a short version of the Job Anxiety Scale - Bjarne Schmalbach; Andreas Kalkbrenner; Markus Bassler; Andreas Hinz; Katja Petrowski (BMC Medical Research Methodology, 2020)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12874-020-01166-w .